Poder, tradición e historia del arte: Apariencia desnuda. La obra de Marcel Duchamp - López Sánchez, Enrique (Anales de Historia del Arte, 2006)
After the Tlatelolco massacre in 1968 Octavio Paz left the Mexican embassy in India and became a cultural leader in Mexico. This paper relates his cultural leadership and the poet’s research and writings about Marcel Duchamp between 1968 and 1978. His vindication of the figure of the French artist in the 70s in Mexico pushed Octavio Paz to defend an experimental and modern aesthetics, based on the artist’s freedom and the values of romantic and avant-garde tradition in a difficult moment for Mexican official culture. Octavio Paz analysed the concepts of creativity, modern artist, tradition and translation in order to create a new cultural discourse opposed to the Mexican society of the 70s.